Ostreid herpes virus 1 infection in families of the Pacific oyster, Crassostrea gigas, during a summer mortality outbreak: Differences in viral DNA detection and quantification using real-time PCR - Sauvage, Christopher; Pepin, Jean-francois; Lapegue, Sylvie; Boudry, Pierre; Renault, Tristan (Virus Research, 2009)
Ostreid herpes virus 1 (OsHV-1) infections, notably reported in Europe and the USA, are closely associated with significant mortalities of the Pacific oyster, Crassostrea gigas, especially during its early stages of life. In summer 2006, we monitored mortality by strict daily verification of three full-sib families of oysters reared under common conditions. We quantified OsHV-1 using real-time PCR in dead and living individuals during and after a mortality event. Mortality events were severe and brief, but significantly different between tested families (cumulative mortality ranging from 1.2 to 49%). Real-time PCR assays revealed different viral DNA loads in dead individuals from different families (P < 0.001). Moreover, the mean level of infection among families was correlated with mortality (P < 0.05). Living oysters showed a significantly lower amount of viral DNA compared with dead ones. This is the first experiment showing the daily changes of individual OsHV-1 DNA load during a mortality outbreak. Our results also support the previously reported high genetic basis underlying the variance of resistance of Pacific oyster to summer mortality, suggesting that there might be a possibility to improve resistance to OsHV-1 by selective breeding.